Effect of varied planting time and dehaulming on the yield potential, processing quality and economic benefit in potato (Bangladesh Journal of Agricultural Research, 2017)
A field experiment was conducted for producing higher processing grade tuber yield and quality by evaluating in relation to different planting times (31 October, 15 and 30 November) and dehaulming dates (80, 90 and 100 days after planting) during 2012-13 potato growing season at Bangladesh Agricultural Research Institute, Gazipur. Results revealed that different growth parameters like plant height, leaves number per hill and foliage coverage were significantly influenced by planting times. Processing and non processing grade tuber number and yield were significantly affected by all the treatments and their interaction. Significantly higher yield of processing grade tuber were recorded in November 15 planting in combination with all the dehaulming dates, ranged from 20.67 to 21.50 t/ha. Processing quality parameters like specific gravity, dry matter, reducing sugar content were significantly varied by planting times, dehaulming dates and their interaction. Whereas the potato chips colour score were not affected by the planting time and dehaulming but all the processing quality parameters were remained in acceptable range. The highest net return (Tk 1,68,404/ha) with a BCR of 1.93 was obtained in November 15 planting with dehaulming at 90 days after plantingBangladesh J. Agril. Res. 42(2): 273-288, June 2017